Peningkatan Produktivitas Kerja Karyawan Melalui Pengawasan Kerja, Budaya Kerja Dan Lingkungan Kerja - Yuningsih, Nining; Maryadi, Adi; Rustianah, Rustianah (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
Human resource management plays a very important role for the company in order to provide maximum results besides that it will also have the best professionalism that can be relied upon to achieve the company's goals and objectives, namely getting maximum profit. This study aims to analyze the effect of work supervision, work culture, and work environment on employee productivity at PT ABC. The company has goals to achieve, and it is highly expected that workers want to work according to the standards set by the company, and the company wants its employees to work very productively. The sample for this survey was 69 respondents who answered. This research uses quantitative methods using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, multiple regression tests, t tests and F tests with the help of SPSS statistics.